A Voltammetry Potentiostat Design for Large Dynamic Range Current Measurement - Yi-Fan Liang; Chun-Yueh Huang; Bin-Da Liu (2011 International Conference on Intelligent Computation and Bio-Medical Instrumentation, 2011)
In this paper, we design a voltammetry potentiostat for the signal processing of electrochemical biosensors. By means of a current range detector and multi-ratio current mirrors, the measured currents of biosensors can be scaled to a proper magnitude of currents. So, the proposed potentiostat can be applied in the biosensors with large dynamic range current variation. The measured biosensor current is converted to a frequency-modulated pulse waveform, whose frequency is proportional to the magnitude of the biosensor current. The simulation results show that the detectable range of the biosensor's current is from 10 nA to 1 mA.